Dynamic Linkages between Social Expenditures and Economic Growth: the Most Important Conclusions for Central European Countries - Tuncer Govdeli; Esra Karakus Umar (Comparative Economic Research. Central and Eastern Europe, 2021)
The role of the state within the neoliberal system is discussed in the approaches developed for social expenditures. Accordingly, the question of whether the state should stand back or provide the support needed by individuals has shaped the literatur\~ne on social expenditures. It is thought that the increase in social expenditures affects public expenditures, and public expenditures may indirectly cause budget deficits. In addition, it is said that there is a decrease in social spending during periods of economic growth. All these dilemmas show that the idea that the country needs both producers and consumers while realizing economic growth has been pushed into the background. Here, the analyses of the relationship between social spending and economic growth are the arguments for the accuracy of this assumption. The aim of this study is to empirically analyze the long-term relationship between the economic growth and social expenditures of eight Central European countries and the causality relationship for 1999 and 2019. In the empirical findings, the cointegration relationship was determined between economic growth and social spending. Based on the findings of the causality analysis, it has been concluded that there is a bidirectional causality relationship between economic growth and social expenditures. Policy proposals are given in the conclusion section of the article.
Keywords: H53; I38; F43; O47; 330; social expenditures; economic growth; political economy; Central European countries; panel data